1991
DOI: 10.1021/tx00019a017
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the in vitro conversion of haloperidol to a potentially neurotoxic pyridinium metabolite

Abstract: Evidence that partially oxidized piperidine derivatives such as the Parkinsonian inducing agent 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) are biotransformed in a reaction catalyzed by monoamine oxidase B (MAO-B) to neurotoxic pyridinium metabolites led to studies resulting in the identification of the haloperidol-derived pyridinium metabolite in the urine of drug-treated rats. The present in vitro studies examine the metabolic pathway governing this overall four-electron oxidation. Although haloperid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 32 publications
1
53
0
1
Order By: Relevance
“…In the neuronal and lymphocyte cell lines, SH-SY5Y and U973, Heiser et al [13] reported significantly lower ATP levels after incubation with HAL. In our study, CPZ had an IC50 on ATP production lower than HAL, a finding possibly explained by the failure of endothelial cells to generate the more potent neurotoxic metabolite HPTP (1,2,3,6-tetrahydropyridine) from HAL [14].…”
Section: Alamar Blue and Intracellular Atp Assaymentioning
confidence: 45%
“…In the neuronal and lymphocyte cell lines, SH-SY5Y and U973, Heiser et al [13] reported significantly lower ATP levels after incubation with HAL. In our study, CPZ had an IC50 on ATP production lower than HAL, a finding possibly explained by the failure of endothelial cells to generate the more potent neurotoxic metabolite HPTP (1,2,3,6-tetrahydropyridine) from HAL [14].…”
Section: Alamar Blue and Intracellular Atp Assaymentioning
confidence: 45%
“…1. These include 1) glucuronidation of the 3 0 alcohol moiety (Someya et al, 1992); 2) reduction of the carbonyl group by cytosolic carbonyl reductase, which leads to reduced HP (Eyles and Pond, 1992); 3) reverse oxidation of reduced HP back to HP (Pan et al, 1998); 4) N-dealkylation leading to the formation of 4-(4-chlorophenyl)-4-hydroxypiperidine (CPHP) (Fang et al, 2001); 5) dehydration of 3 0 alcohol moiety to 4-(4-chlorophenyl)-1-[4-(4-fluorophenyl)-4-oxobutyl]-1,2,3,6-tetrahydropyridine (HPTP) (Subramanyam et al, 1991a;Van der Schyf et al, 1994) , 1997). In contrast to earlier studies (Llerena et al, 1992;Viala et al, 1996) that suggested the involvement of cytochrome P450 (P450) 2D6 in HP metabolism to CPHP, HPTP, and HPP ϩ , recent reports have indicated that these pathways are almost exclusively catalyzed by CYP3A4 (Usuki et al, 1996;Fang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…1. These include 1) glucuronidation of the 3 0 alcohol moiety (Someya et al, 1992); 2) reduction of the carbonyl group by cytosolic carbonyl reductase, which leads to reduced HP (Eyles and Pond, 1992); 3) reverse oxidation of reduced HP back to HP (Pan et al, 1998); 4) N-dealkylation leading to the formation of 4-(4-chlorophenyl)-4-hydroxypiperidine (CPHP) (Fang et al, 2001); 5) dehydration of 3 0 alcohol moiety to 4-(4-chlorophenyl)-1-[4-(4-fluorophenyl)-4-oxobutyl]-1,2,3,6-tetrahydropyridine (HPTP) (Subramanyam et al, 1991a;Van der Schyf et al, 1994); 6) oxidation of the piperidin-4-ol moiety in HP to the corresponding 4-(4-Chlorophenyl)-1-[4-(4-fluorophenyl)-4-oxobutyl]-pyridinium (HPP ϩ ) metabolite (Usuki et al, 1996) P450, cytochrome P450; DMSO, dimethyl sulfoxide; SSRI, selective serotonin reuptake inhibitor; LC-MS/MS, high performance liquid chromatography-tandem mass spectrometry; HPLC, high performance liquid chromatography; R t , retention time; CID, collision-induced dissociation; NPP † , N-nonyl-4-phenylpyridinium. al., 1997). In contrast to earlier studies (Llerena et al, 1992;Viala et al, 1996) that suggested the involvement of cytochrome P450 (P450) 2D6 in HP metabolism to CPHP, HPTP, and HPP ϩ , recent reports have indicated that these pathways are almost exclusively catalyzed by CYP3A4 (Usuki et al, 1996;Fang et al, 2001).…”
mentioning
confidence: 99%
“…Iminium ion formation also presumably involves oxidation at the piperidine ring ␣-carbons (Castagnoli et al, 1997). Furthermore, in certain cases (e.g., haloperidol), the N-substituted piperidines are known to undergo oxidative conversion to potentially neurotoxic pyridinium species; this conversion may also occur via a pathway that initiates with an ␣-carbon oxidation (Subramanyam et al, 1991). One possible strategy to overcome these drawbacks of the unsubstituted piperidine is the use of a 2,2,6,6-tetramethyl-piperidine moiety (2,2,6,6-TMPi 1 ) that would block the oxidation at the ␣-carbons.…”
mentioning
confidence: 99%